The generation of induced pluripotent stem cells for macular degeneration as a drug screening platform: identification of curcumin as a protective agent for retinal pigment epithelial cells against oxidative stress - Chang, Yun-Ching; Chang, Wei-Chao; Hung, Kuo-Hsuan; Yang, Der-Ming; Cheng, Yung-Hsin; Liao, Yi-Wen; Woung, Lin-Chung; Tsai, Ching-Yao; Hsu, Chih-Chien; Lin, Tai-Chi; Liu, Jorn-Hon; Chiou, Shih-Hwa; et al. (Frontiers in Aging Neuroscience, 2014)
Age-related macular degeneration (AMD) is one retinal aging process that may lead to irreversible vision loss in the elderly. Its pathogenesis remains unclear, but oxidative stress inducing retinal pigment epithelial (RPE) cells damage is perhaps responsible for the aging sequence of retina and may play an important role in macular degeneration. In this study, we have reprogrammed T cells from patients with dry type AMD into induced pluripotent stem cells (iPSCs) via integration-free episomal vectors and differentiated them into RPE cells that were used as an expandable platform for investigating pathogenesis of the AMD and in-vitro drug screening. These patient-derived RPEs with the AMD-associated background (AMD-RPEs) exhibited reduced antioxidant ability, compared with normal RPE cells. Among several screened candidate drugs, curcumin caused most significant reduction of ROS in AMD-RPEs. Pre-treatment of curcumin protected these AMD-RPEs from H2O2-induced cell death and also increased the cytoprotective effect against the oxidative stress of H2O2 through the reduction of ROS levels. In addition, curcumin with its versatile activities modulated the expression of many oxidative stress-regulating genes such as PDGF, VEGF, IGFBP-2, HO1, SOD2 and GPX1. Our findings indicated that the RPE cells derived from AMD patients have decreased antioxidative defense, making RPE cells more susceptible to oxidative damage and thereby leading to AMD formation. Curcumin represented an ideal drug that can effectively restore the neuronal functions in AMD patient-derived RPE cells, rendering this drug an effective option for macular degeneration therapy and an agent against aging-associated oxidative stress.